Representasi Matematis sebagai Mediator Pembentukan Makna - Sri Asnawati (Euclid, 2026)
Mathematical representations play a fundamental role in mathematics learning as they mediate meaning making, conceptual understanding, and students’ mathematical activity. In higher education, representations become increasingly critical due to the growing complexity of mathematical concepts and the need to coordinate symbolic, graphical, verbal, and visual forms. However, research indicates that university mathematics instruction often prioritises symbolic manipulation, leading students to experience difficulties in coordinating and transforming multiple representations. This article aims to systematically synthesise research on undergraduate students’ mathematical representations from a semiotic–representational perspective. A systematic literature review was conducted on Scopus-indexed journal articles published between 2014 and 2024. The findings reveal that mathematical representations function as primary epistemic mediators in learning mathematics, and that deep understanding depends on students’ ability to coordinate and translate across representations. The review also shows that the dominance of symbolic representations without meaningful integration of other forms tends to result in fragmented understanding. Based on this synthesis, the article highlights the need to position mathematical representations at the core of higher education mathematics instruction and proposes a conceptual framework that emphasises representational coordination as a foundation for mathematical meaning making.